EFEKTIVITAS MEDIA LEAFLET TERHADAP PENGETAHUAN IBU TENTANG PEMELIHARAAN KESEHATAN GIGI DAN MULUT DI RA NURUL HIKMAH (Jurnal Terapi Gigi dan Mulut, 2022)
Maintenance of dental and oral health is one of the efforts to improve health. The mouth is not just the entrance for food and drink, but the function of the mouth is more than that. One of the most important factors in dental and oral health of early childhood is parents where the mother has the most important role. Mother's lack of knowledge will lead to poor oral health behavior, and vice versa. Efforts to increase knowledge and prevent dental and oral health problems in children are by providing dental and oral health education to parents in need of health promotion, for example by providing counseling or information. This study aims to determine the effectiveness of counseling using leaflet media on mother's knowledge about dental and oral health maintenance at RA Nurul Hikmah. The research method used is analytical research with a quasi-experimental research design. The research design used was a one-group pretest-posttest design. The population of this study amounted to 40 people. The results of this study indicate that the average result of the pre-test counseling is 69.35 and the average post-test counseling result is 95.18. The value of p value on the knowledge of respondents before and after being given leaflet media was (0.000 < 0.05). The conclusion of this study is that leaflet media is effective for increasing mother's knowledge about maintaining oral and dental health.